The Promise of Sociology : Classical Approaches to Contemporary Society, Second Edition. - Beamish, Rob (University of Toronto Press, 2016)
Unlike most introductory texts that take a topical approach to studying sociology, this smart, challenging, and accessibly written text looks at the core principles of the discipline, making links to a contemporary context.